The influence of service quality, Guanxi, value co-creation and corporate image in building developers apartments loyalty toward contractors in apartment construction industry - Augustinus Setijanto; Idris Gautama So; Firdaus Alamsjah; Viany Utami Tjhin (Cogent Business & Management, 2024)
The aim of this research is to examine the influence of service quality, guanxi, value co-creation and corporate image on customer loyalty of developer in the apartment construction industry. This research used an online survey approach, collecting 316 respondent data from apartment developers. This research uses the structured equation modeling method with SmartPLS to test the hypothesis of the research model. The results of the hypothesis test prove that there is a positive and significant influence of service quality, guanxi, value co-creation and corporate image on customer loyalty. This study is one of the few studies that examines customer loyalty in the context of the apartment construction industry, and moreover, this study examines the influence of service quality, guanxi, value co-creation and corporate image on customer loyalty. This research has managerial implications for building apartment contractor companies on how to build and maintain customer loyalty.
Keywords: 650; Customer loyalty; Guanxi; value co-creation; corporate image; service quality; apartment constructions